INFLUERCE OF FOLIAR APPLICATION OF AGROSOL AND ENRAIZAL ON THE QUALITATIVE CHARACTERS OF THE FRUITS OF CHERRY TOMATO GROWN UNDER OPEN FIELD AND PLASTIC HOUSE CONDITIONS - & Sadik, Salman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A Field experiment was conducted on the vegetable field - Department of Horticulture - College of Agriculture - University of Baghdad during spring season 2013 and fall season 2013-2014  to study the effect of different levels of Agrosol and Enraizal on the qualitative characters of the fruits of cherry tomato. Hybrid Jaguar,F1 used during spring  season and  fall season and the hybrid Summerbrix  used during fall season only. Three concentrations of Agrosol (0,3,6 g/l ) and Enraizal (0,2,4ml/l) were used respectively .The experiment was conducted by using (RCBD) with three replicates. The results could be summarized as follows: in first experiment, Treatment AG2EN0 increased the percentage of Lycopene content in fruits, vitamin C, fruit acidity at the rates of 289.47%, 15.16%, 91.42% respectively compard to control treatment.In second experiment, Treatment AG1EN2 and treatment AG2EN1 increased Lycopene content in fruit by 82.56% and 29.04% for both hybrids sequentially. Treatment AG1EN1 gave significant increases in beta carotene content in the fruits by 56.97% in hybrid Summerbrix.  Treatment AG1EN1and  AG0EN1 significantlly  increased  vitamin C content in the fruits by 13.58% and 34.09% for both hybrids respectively, while treatments  AG1EN2 and  AG0EN1 significantly increased fruit acidity by 487.20% and 59.03% for both  hybrids respectively . TSS in cherry tomato fruit was increased significantlly at treatment AG2EN1 by 12.21% in hybrid Jaguar,F1. AG0EN2 treatment significantly increased total sugars content in the fruits by 21.47% in hybrid Jaguar,F1 compard to control treatment.